Novel Analytical Solutions to a New Formed Model of the (2+1)-Dimensional BKP Equation using a Novel Expansion Technique - Mia, Rajib (Journal of Applied Nonlinear Dynamics, 2026)
In this article, we present a comprehensive analytical study to obtain the exact traveling wave solutions to a new formed model of the (2+1)-dimensional BKP equation. We construct exact solutions of the considered model using a recently developed expansion technique. This current proposed technique has been successfully implemented to obtain a few exact solutions of a new formed (2+1)-dimensional BKP equation. In order to understand the physical interpretation of solutions effectively, the 2D and 3D graphs are plotted for each type of the solutions obtained for different particular values of the parameters. Furthermore, it is found that the obtained solutions are periodic and solitary wave solutions. We anticipate that the proposed method is reliable and can be applied for obtaining wave solutions of the other nonlinear evolution equations (NLEEs).